Stunting Prevention Strategy Through Empowerment of Pregnant Women and Mothers of Toddlers in The "Siap Genting" and "Sobat Tensi" Programs in Banjar Village, Banyuwangi District: English - Dwi Nanda Rachman; Rifka Pramudia Wardani; Nikita Meilia Prita Dewi; Jayanti Dian Eka Sari; Jr, Fernando B. Garcia (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Stunting is a problem caused by a prolonged lack of nutrition from food and infectious diseases. Based on data from the Indonesian Ministry of Health in 2022, the prevalence of cases was 21.6% in Indonesia and 20.1% in Banyuwangi Regency. One of the Sustainable Development Goals (SDGs) is eliminating hunger, achieving food security and good nutrition, and increasing sustainable agriculture. The problem of stunting is closely related to the health of pregnant women. One of the many health problems that occur in pregnant women is hypertension. Aims: This community empowerment aims to increase the target's knowledge about preventing stunting and hypertension. Methods: This activity uses a socialization approach to the target group consisting of 24 pregnant women and mothers of toddlers with lecture methods, discussions and continued direct screening for 3 hours. Results: High engagement was indicated by participation in this socialization activity, questions and answers during the event and enthusiasm to follow the screening session. Conclusions: Targeted participants demonstrated increased knowledge through their ability to answer questions and plan follow-up. This initiative significantly increased participants' knowledge, awareness, and engagement to be able to take care of their babies' health and safeguard their health from the dangers of hypertension.